Lightning: a bolt from the blue - Ab Kadir, Mohd Zainal Abidin (Universiti Putra Malaysia Press, 2017)
To the electric utility engineer, the parameters of the flash that are of primary interest are the crest current for the first and subsequent strokes, the waveshape of these currents, correlation between the parameters, the number of strokes per flash and flash incidence rates where the ground flash density is denoted as flashes per square km-year and symbolised by Ng. The first three parameters, as we know them today, are to a very large extent based on the measurements of Berger. Berger’s masts, 70 and 80 metres high, were mounted atop Mt. San Salvatore (Switzerland), which is 650 metres above Lake Lugano, where it can be readily noted that these 125 records represent one of the best and most extensive sets of data available to the industry to date. This inaugural talk focuses on the lightning severity scenario in Malaysia, which could also be applicable to other tropical countries, and some of the useful parameters for lightning protection system design and forensic study. Some specific engineering applications and solutions are summarised, taking into account various lightning parameters, available from past and current measurements. These include the first national circular on lightning protection system installation for buildings, lightning protection guide on building and recently released guidebook on lightning protection for photovoltaic (PV) systems published by the Energy Commission of Malaysia and Sustainable Energy Development Authority (SEDA), respectively. It is He who shows you lightning, [causing] fear and aspiration, and generates the heavy clouds. And the thunder exalts [Allah] with praise of Him - and the angels [as well] from fear of Him - and He sends thunderbolts and strikes therewith whom He wills while they dispute about Allah; and He is severe in assault. [Ar-Ra’ad: 12-13]